Changes in the prevalence of diabetes and control of risk factors for diabetes among Chinese adults from 2007 to 2017: An analysis of repeated national cross‐sectional surveys - Chenye Jin; Yaxin Lai; Yongze Li; Di Teng; Wenying Yang; Weiping Teng; Zhongyan Shan; For the China National Diabetes and Metabolic Disorders Study Group and the Thyroid Disorders, Iodine Status and Diabetes Epidemiological Survey Group (Journal of Diabetes, 2024)
Abstract Introduction To examine changes in the prevalence of diabetes and the control of risk factors for diabetes over 10 years among adults in China. Methods Two population‐based cross‐sectional surveys were used to obtain a nationally representative sample of adults aged 20 years and older in mainland China in 2007 (n = 46 239) and 2017 (n = 73 340). Changes in the prevalence of diabetes, impaired fasting glucose, impaired glucose tolerance, and prediabetes, as diagnosed by the World Health Organization criteria, were assessed over time. Results The weighted prevalence of diagnosed diabetes (3.8% vs 6.3%, p = .0001) and total diabetes (9.7% vs 11.7%, p = .005) increased among the overall population between 2007 and 2017. The weighted prevalence of undiagnosed diabetes (5.9% vs 5.4%, p = .7), impaired fasting glucose (2.7% vs 2.6%, p = .68), impaired glucose tolerance (12.7% vs 12.5%, p = .95), prediabetes (15.4% vs 15.1%, p = .79), the treatment of diabetes (34.1% vs 32.5%, p = .44), and the control of diabetes (31.1% vs 32.8%, p = .73) did not significantly change over this period. The awareness of diabetes (39.4% vs 53.6%, p = .0004) increased over 10 years among the overall population. The proportion of achieved high‐density lipoprotein cholesterol targets increased (p = .005), but the proportion of achieved body mass index (p = .01) and waist circumference (p = .0002) targets decreased significantly. Conclusions Between 2007 and 2017, the prevalence of total diabetes (diagnosed by the World Health Organization criteria), especially diagnosed diabetes, increased among adults in China. Although awareness of diabetes improved, effective interventions and clinical strategies are urgently required.